“Lady Orlando”: tirésias literário e a representação feminina na obra de Virginia Woolf - França, Juliana de Lima (2019)
This dissertation investigates the work of Virginia Woolf and her relationships with the multiple identities of gender and feminine representation in the early twentieth century. The research has as main source the novel Orlando, published in 1928, whose plot of a protagonist who changes sex in the middle of history, makes visible the thematic of the displacement of the identity and position of woman in society. The analysis is organized into three chapters. In the first one, a dialogue is sought between History and Literature and how the author uses the artifice of the biography in the novel to subvert both, as well as the relationship between the author, work and period, which occurs in a complex plot. Next, the feminine representation in the work is discussed and how the author advocates for the equality of rights and for the intellectual emancipation of women. And finally, it is discussed the socially built notions of identity and gender. Other issues adressed are the performativity present in the work and how clothes play an important role in the constitution of the becoming of the individual